MEMAHAMI PENGALAMAN PRASANGKA DAN DISKRIMINASI SOSIAL YANG DIALAMI OLEH PEMILIK TATO - Pertiwi, Bunga; Manalu, S. Rouli; Noor Rakhmad, Wiwid (Interaksi Online, 2024)
This study aims to understand the experiences of tatto owners related to experiences of This study aims to understand the experiences of tattoo owners related to experiences of prejudice and discrimination experienced in the community using a phenomenological approach. The focus of this study is the subjective experiences of tattoo owners who experience stigma, prejudice and discrimination from family, social environment, or work. This study uses Symbolic Interactionism Theory which examines how the meaning of tattoos is constructed through social interactions which then give rise to stigma, prejudice and discriminatory actions against tattoo owners. The interpretive paradigm used in this study is Interpretative Phenomenological Analysis (IPA) which helps researchers to explore in depth the personal experiences of informants. Data were collected through in-depth interviews with six individuals who have permanent tattoos on their bodies from various social and cultural backgrounds. The results of the study showed that male tattoo owners are often perceived with criminal acts such as drug addicts, pickpockets, being rude, thugs. Female tattoo owners are associated as bad women and naughty women. In addition, dynamics of change in the social environment were found before and after having a tattoo. Tattooed individuals experience prejudice and discrimination after they have tattoos on their bodies. Manifestations of prejudice are manifested through marginalization in the workplace, as well as exclusion in everyday social interactions.